2020
DOI: 10.3889/oamjms.2020.5446
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease-19: Public Health Nurses’ Knowledge, Attitude, Practices, and Perceived Barriers in Indonesia

Abstract: BACKGROUND: The coronavirus disease (COVID)-19 outbreaks and its rapid rise in prevalence has been a major concern internationally. We conducted a short survey to understand the knowledge, attitude, and practices regarding COVID-19 and estimated barriers to disease transmission perceived by public health nurses (PHN) in Indonesia. AIM: The study aimed to identify the association of sociodemographic characteristic with knowledge, attitude, and practices regarding COVID-19 among PHNs in Indonesia and highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 23 publications
(38 reference statements)
1
16
0
Order By: Relevance
“…Based on the independent T-test result, we can conclude that health students have significantly higher scores of COVID-19 knowledge than social students (p<0.001). This finding is in line with a study conducted by Kistan et al and Sahar et al which stated that health students' knowledge about the prevention of COVID-19 in Indonesia was classified as good [20], [21]. A study was done by Alzoubi et al also reported that health science students had a high knowledge of COVID-19, while social science students had low knowledge [18].…”
Section: Figure 1 Student's Level Of Knowledgesupporting
confidence: 88%
“…Based on the independent T-test result, we can conclude that health students have significantly higher scores of COVID-19 knowledge than social students (p<0.001). This finding is in line with a study conducted by Kistan et al and Sahar et al which stated that health students' knowledge about the prevention of COVID-19 in Indonesia was classified as good [20], [21]. A study was done by Alzoubi et al also reported that health science students had a high knowledge of COVID-19, while social science students had low knowledge [18].…”
Section: Figure 1 Student's Level Of Knowledgesupporting
confidence: 88%
“…Based on the results of the literature search found 21 articles (Table 1) generally assessed the knowledge, attitudes, practices, perceptions, anxiety, and psychological responses of nurses related to COVID-19. Four articles were found in China (Chen et al, 2020;Huang et al, 2020;Jin & Yi, 2020;Li et al, 2020), two in Arabian (Al-Dossary et al, 2020;Alreshidi, 2020), two in India (Adhikari et al, 2020;Patidar et al, 2020), one in Nepal (Kafle et al, 2020), three in Turkey (Aydin & Balci, 2020;Gumus & Basgun, 2020;Semerci et al,2020), one in Northern Ethiopia (Tadesse et al, 2020), two in Pakistan (Alwani et al, 2020;Zafar et al, 2020), one in Iran (Nemati et al, 2020), one in Lebanon (Saadeh et al,2020), one in Ghana (Buertey et al, 2020), one in Indonesia (Sahar et al, 2020), one in Bangladesh (Saha, et al, 2020), and one in Egypt (Goda Elbqry, 2020). The number of samples between 85-1.323 nurses, using a questionnaire as an instrument, the study used a cross-sectional study.…”
Section: Resultsmentioning
confidence: 99%
“…Research in Ghana, nurses show that the level of preventive practice has been recorded to be good (Buertey et al, 2020). Research in Indonesia, of 368 PHN nurses, nurses had good practices related to COVID-19, factors related to practice were gender, and resources (Sahar et al, 2020). Research in Bangladesh, 73.42% of nurses have good practice, 21.84% moderate practice, and 8.68% bad practice, there is a significant relationship between knowledge and practice of nurses (Saha et al, 2020).…”
Section: Practice Related To Covid-19mentioning
confidence: 97%
See 2 more Smart Citations